IMPROVING THE EXPERIENCE OF DIAGNOSIS IN PARKINSON'S DISEASE. Issue 12 (15th November 2016) - Blight, Ben; Davis, Jane; Evans, Val; Hawkes, Nicola; Carroll, Camille
Abstract : Background and aims: Receiving a Parkinson's (PD) diagnosis should leave patients feeling supported, empowered and fully involved in the management of their condition. A patient identified that too often patients feel vulnerable and confused following diagnosis. We aimed to evaluate current patient experience across the South West to identify factors that could be improved upon and design improvement strategies that can be easily implemented. Methods: A 17 item questionnaire, designed by clinicians and patients to evaluate experience of the diagnosis was sent to 101 newly-diagnosed patients across the South West of England. Results: 40 responses were received; mean age was 68.7 yrs, 66.7% male. The main findings were: failure to advise companion to clinic appointment 55%; failure to signpost Parkinson's UK 55%; inadequate follow-up information 46%; inadequate written information 31%; not involving patients in treatment decisions 25%; not sending copies of clinic letters 22%; not providing PD nurse contact details 28%; inadequate consultation time 13%. Conclusions: As a result of these findings, we will design a local 'contact' sheet that can be provided to patients at diagnosis, including information about Parkinson's and how to access Parkinson's UK resources and specialist nurses. Physicians should fully explain treatment choices to patients and ensure patients are copied into clinic letters. Follow-up arrangements should be timely and clearly communicated. Physicians will be encouraged to design their new-patient service based on the UK Parkinson's Excellence Network's Document (2015), 'Improving the diagnosis experience for people with Parkinson's'.